The Prophet Muhammad's Love Education: The Concept of Islamic Parenting and Parents' Responsibilities Towards Their Children - Yuliani Khalfiah; Hamdanah Hamdanah; Mazrur Mazrur (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This article examines the concept of love-based upbringing in Islamic parenting as reflected in the Hadiths of the Prophet Muhammad (peace be upon him) through an interdisciplinary approach combining Hadith studies and developmental psychology. The study aims to analyze parental educational responsibilities as depicted in the Prophetic traditions and to integrate these insights with Attachment Theory developed by John Bowlby and Mary Ainsworth. This research employs a qualitative library research method, using primary sources from major Hadith compilations, particularly Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, alongside secondary sources from Islamic education and child development literature. The findings reveal that the Prophetic model of parenting is fundamentally grounded in compassion (raḥmah), gentleness (rifq), and attentiveness to children's emotional needs. The integration of Attachment Theory demonstrates that the Prophetic parenting practices align closely with the principles of secure attachment, particularly parental responsiveness and emotional availability. This study contributes a conceptual framework of Islamic parenting based on love-based upbringing, offering a holistic model that remains relevant to the emotional, moral, and spiritual development of Muslim children in contemporary contexts.